An analysis of the sexual orientation discrimination framework in the public sector : the case of Stellenbosch Municipality - Opperman, Theo (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (Public and Development Management))--University of Stellenbosch, 2009.